2005
DOI: 10.1159/000083966
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Relationships with Parents and Paranoid Delusions: Comparisons of Currently Ill, Remitted and Normal Participants

Abstract: Background: Paranoid delusions are associated with abnormal attributions and abnormal beliefs about the self. Some researchers have also reported an association between paranoid beliefs and abnormal attachment representations. Sampling and Methods: Perceptions of relationships with the family of origin were measured in 14 currently ill paranoid patients, 9 remitted paranoid patients and 15 healthy controls, using two methods: the Parental Bonding Instrument (PBI), and the Relationship with Family of Origin Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 90 publications
3
20
2
Order By: Relevance
“…It is unsurprising, then, that the nature of our family relationships can color our thoughts about and attitudes towards people more generally: while family identification is likely to promote feelings of trust in others (e.g., Kramer et al, 2014), lack of family identification is likely to promote loneliness and isolation (Sani, 2012): conditions which may foster paranoid thoughts. Indeed, there is a range of evidence to suggest that problematic interactions with family members (which are often associated with low family identification) can lead to paranoia (e.g., Bentall et al, 2012;Myhrman et al, 1996;Rankin et al, 2005). Our findings lend weight to these studies, but extend them by explicitly exploring the relationship between family identification and paranoia, rather than inferring it from observing the relationship between problematic family interactions and paranoia.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is unsurprising, then, that the nature of our family relationships can color our thoughts about and attitudes towards people more generally: while family identification is likely to promote feelings of trust in others (e.g., Kramer et al, 2014), lack of family identification is likely to promote loneliness and isolation (Sani, 2012): conditions which may foster paranoid thoughts. Indeed, there is a range of evidence to suggest that problematic interactions with family members (which are often associated with low family identification) can lead to paranoia (e.g., Bentall et al, 2012;Myhrman et al, 1996;Rankin et al, 2005). Our findings lend weight to these studies, but extend them by explicitly exploring the relationship between family identification and paranoia, rather than inferring it from observing the relationship between problematic family interactions and paranoia.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, there is evidence to suggest that these negative interpersonal experiences with family members could actually foster greater feelings of paranoia towards other people in general. For instance, Rankin, Bentall, Hill, and Kinderman (2005) found that paranoid patients have negative beliefs about their families which persist even after recovery, while Myhrman, Rantakallio, Isohanni, Jones, and Partanen (1996) showed that being unwanted by one's parent/s at birth increases the risk of psychosis. Additionally, Bentall, Wicknall, Shevlin, and Varese (2012) explored the 2007 Adult Psychiatric Morbidity Survey, and found a positive relationship between being brought up in institutional care and paranoia.…”
Section: Aim and Overview Of Researchmentioning
confidence: 99%
“…Self-rated bonding behavior to parents has often been used as representative of parental attachment relationships [14][15][16].The PBI was developed by Parker et al in 1979 [17]. Its Chinese version was written and revised in 1999 [18].…”
Section: Instrumentsmentioning
confidence: 99%
“…In a recent study of perceived relationships with parents and paranoid delusions, in comparisons of currently ill, remitted and normal participants, Rankin, Bentall, Hill, and Kinderman (2005) concluded that dysfunctional relationships are a common feature of paranoid patients, perhaps contributing to paranoid thinking, supporting the association previously shown between paranoid beliefs and abnormal attachment representations echoed in the findings of Clare et al (2000).…”
Section: Developmental Understanding Of Violencementioning
confidence: 53%